Hegemonic Masculinity Attitudes Toward Female Genital Mutilation/Cutting Among a Sample of College Students in Northern and Southern Sierra Leone. (September 2020) - Small, Eusebius; Sharma, Bonita B.; Nikolova, Silviya Pavlova; Tonui, Betty C.
Introduction: Female genital mutilation or cutting (FGM/C) is a public health problem. Approximately three million women and girls undergo FGM/C every year, worldwide. The purpose of the study was to assess the influence of education on hegemonic masculinity attitudes between male and female students and whether parental education differentiated the groups.Method: A cross-section design was used. Data were collected through a survey response from 338 students in May 2017. The data were analyzed using chi-square and correlational tests.Results: Education did not change the attitudes of students toward FGM/C (χ 2 = 3.64, p = .16); however, parental education had an influence on both male and female students' attitudes toward FGM/C.Discussion: The study suggests that education alone may not be sufficient to end FGM/C practice. A comprehensive community-led strategy incorporating culturally congruent health care to involve multiple parties of health professionals, religious leaders, government, and policy makers may be needed to address the problem.